2007
DOI: 10.1093/jjco/hym117
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine and Cisplatin Chemotherapy (XP) Alone or Sequentially Combined Chemoradiotherapy Containing XP Regimen in Patients with Three Different Settings of Stage IV Esophageal Cancer

Abstract: The similar OS in patients with M1a and M1b nonvisceral LN metastases suggests that concurrent chemoradiotherapy might contribute in the latter. Our findings indicate that sequentially combined chemoradiotherapy containing XP regimen was active and well tolerated as first-line treatment for M1a as well as M1b esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…A milestone phase III study of 316 patients with gastric cancer demonstrated that the capecitabine arm was not inferior to the 5-FU arm in terms of PFS (5.6 months versus 5.0 months) and OS (10.5 months versus 9.3 months) [ 17 ]. Based on studies performed with patients with gastric or esophageal adenocarcinoma, capecitabine is often used in combination with cisplatin [ 18 ]. However, it is well known that cisplatin is associated with significant toxicity and usually requires a high level of clinical monitoring and supportive care.…”
Section: Discussionmentioning
confidence: 99%
“…A milestone phase III study of 316 patients with gastric cancer demonstrated that the capecitabine arm was not inferior to the 5-FU arm in terms of PFS (5.6 months versus 5.0 months) and OS (10.5 months versus 9.3 months) [ 17 ]. Based on studies performed with patients with gastric or esophageal adenocarcinoma, capecitabine is often used in combination with cisplatin [ 18 ]. However, it is well known that cisplatin is associated with significant toxicity and usually requires a high level of clinical monitoring and supportive care.…”
Section: Discussionmentioning
confidence: 99%
“…Evans et al [19] Tsai et al [20] used carboplatin (area under the ROC curve AUC = 2) on day 1 and 8, docetaxel Lee et al [21] used two cycles of XP induction chemotherapy, consisting of capecitabine 1000 mg/m The median time of progression was 7.8 mo (95% CI, 6.0-9.5 mo) and the median overall survival was 12.0 mo (95% CI, 9.0-15.0 mo). Evans et al [22] used a regimen comprised of docetaxel 40 mg/m 2 , on day 1 and 8, carboplatin (AUC = 2) on day 1 and 8, and capecitabine 2000 mg/m 2 , on days 1-10 in a 21-day cycle.…”
Section: Qin Tj Et Al Oxaliplatin Plus Capecitabine In Metastatic Esccmentioning
confidence: 99%
“…In some studies, radiotherapy was administered to patients after induction chemotherapy. For instance, Lee et al [ 17 ] treated 74 patients with stage IV EC with two cycles of induction chemotherapy, after which patients classified as M1a and M1b (nonvisceral lymph node metastases) were treated with 54 Gy of radiotherapy concurrently with weekly capecitabine and CDDP. Only three out of 18 M1a patients (16.7%) and four out of 27 M1b patients (14.8%) attained PR after induction chemotherapy.…”
Section: Discussionmentioning
confidence: 99%